1992
DOI: 10.1080/01635589209514196
|View full text |Cite
|
Sign up to set email alerts
|

Diet and prognosis of breast cancer

Abstract: The relationship between the occurrence of breast cancer and dietary intake, in particular a high-fat diet, has attracted much attention in recent years. In addition, the prognosis of breast cancer patients on the basis of dietary intake is also an interesting subject. The present study utilized breast cancer patients whose dietary intake was carefully assessed about one decade previously in a case-control study to determine whether dietary intake was indeed related to the patients' prognosis. The study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…In contrast, the Nurses' Health Study did not conclude that a low fat diet after diagnosis leads to a survival advantage [53]. The same conclusion was reached by a prospective study of 213 breast cancer patients in Japan; it should be remarked that Japanese women develop breast cancer at an earlier age and consume relatively small amounts of fat (mean dietary fat intake was about 23% of calories) [54].…”
Section: Dietary Fatmentioning
confidence: 95%
“…In contrast, the Nurses' Health Study did not conclude that a low fat diet after diagnosis leads to a survival advantage [53]. The same conclusion was reached by a prospective study of 213 breast cancer patients in Japan; it should be remarked that Japanese women develop breast cancer at an earlier age and consume relatively small amounts of fat (mean dietary fat intake was about 23% of calories) [54].…”
Section: Dietary Fatmentioning
confidence: 95%
“…Of the few studies that have investigated the relationship between dietary fat and survival from breast cancer (3)(4)(5)(6)(7), two (3,6) showed decreased survival in association with a relatively high fat intake, whereas the remainder showed no association. However, adjustment for energy intake was not performed in any of these studies, and it is not clear whether the positive findings reflect an association with fat per se or whether they arose as a result of confounding by energy intake.…”
Section: Introductionmentioning
confidence: 94%
“…Premorbid dietary factors have been analyzed in relation to the survival of patients who are affected by breast carcinoma, [12][13][14][15][16][17] pancreatic and prostate carcinoma, 18 lung carcinoma, 19 and laryngeal carcinoma. 20 Whereas some of these studies were negative, others showed an improved survival associated with high vegetable consumption (or with high intake of nutrients from vegetable sources) and a worse prognosis associated with high fat intake.…”
Section: Discussionmentioning
confidence: 99%